2018
DOI: 10.1037/xlm0000532
|View full text |Cite
|
Sign up to set email alerts
|

Listeners and readers generalize their experience with word meanings across modalities.

Abstract: Research has shown that adults’ lexical-semantic representations are surprisingly malleable. For instance, the interpretation of ambiguous words (e.g., bark) is influenced by experience such that recently encountered meanings become more readily available (Rodd et al., 2016, 2013). However, the mechanism underlying this word-meaning priming effect remains unclear, and competing accounts make different predictions about the extent to which information about word meanings that is gained within one modality (e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
70
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(80 citation statements)
references
References 91 publications
9
70
1
Order By: Relevance
“…However recent evidence suggests that similar mechanisms may support learning about word meanings. Gaskell et al, (2018) found that the magnitude of word-meaning priming seen after 12 or 24 hours is significantly boosted when the learning takes place immediately before a period of sleep. This suggests that the short-term boost in word meaning availability that is seen at intervals of 20-40 minutes (e.g., Rodd et al, 2016) may not reflect a long-term resilient change to the stored mental lexicon, and that it is only with sleep that the knowledge acquired about word-meaning availability is integrated into the lexicon.…”
Section: Importance Of Learning Mechanisms In the Maintenance Of Highmentioning
confidence: 94%
See 1 more Smart Citation
“…However recent evidence suggests that similar mechanisms may support learning about word meanings. Gaskell et al, (2018) found that the magnitude of word-meaning priming seen after 12 or 24 hours is significantly boosted when the learning takes place immediately before a period of sleep. This suggests that the short-term boost in word meaning availability that is seen at intervals of 20-40 minutes (e.g., Rodd et al, 2016) may not reflect a long-term resilient change to the stored mental lexicon, and that it is only with sleep that the knowledge acquired about word-meaning availability is integrated into the lexicon.…”
Section: Importance Of Learning Mechanisms In the Maintenance Of Highmentioning
confidence: 94%
“…They also have revealed several important characteristics of the underlying mechanism(s) that supports this learning. Gilbert et al, (2018) examined the extent to which information about word meanings that is gained within one modality (e.g., speech) is transferred to the other modality (e.g., reading). In these experiments ambiguous target words were primed with either written or spoken sentence.…”
Section: Importance Of Learning Mechanisms In the Maintenance Of Highmentioning
confidence: 99%
“…In addition to these long-term effects of experience, recent experimental evidence has shown that more encounters with particular, subordinate interpretations of ambiguous words can substantially boost the availability of these primed meanings (Betts, Gilbert, Cai, Okedara, & Rodd, 2018;Gaskell, Cairney, & Rodd, 2019;Gilbert, Davis, Gaskell, & Rodd, 2018;Rodd, Lopez Cutrin, Kirsch, Millar, & Davis, 2013). In word-meaning priming experiments, participants encounter a subordinate meaning of an ambiguous word within a strongly disambiguating sentence context (e.g., "The farmer moved the sheep into the PEN").…”
Section: (Iii) Contextual Modulation Of Unambiguous Word Meaningsmentioning
confidence: 99%
“…Then, after a delay (typically 20-40 minutes) the availability of the word's different meanings is assessed using tasks such as word association or semantic relatedness judgement (Betts et al, 2018;Gaskell et al, 2019;Gilbert et al, 2018;Rodd et al, 2016Rodd et al, , 2013. Results from these different paradigms have consistently shown that the availability of the primed, subordinate word meaning is boosted compared to a control, unprimed condition.…”
Section: (Iii) Contextual Modulation Of Unambiguous Word Meaningsmentioning
confidence: 99%
“…First, given the surprising lack of a cognate facilitation effect in Experiment 1, to conduct a direct replication of the pattern of results observed in the bilingual group of Experiment 1. And second, given the successful use of a semantic relatedness task in the monolingual domain to replicate effects of long-term priming with homonyms (Gilbert et al, 2018), to attempt once again to replicate the cross-lingual long-term priming effect demonstrated by Poort et al (2016).…”
Section: Experiments 2 Introductionmentioning
confidence: 99%